THE UTILIZATION OF DIGITAL MARKETING, MARKET ORIENTATION AND PRODUCT INNOVATION ON MARKETING PERFORMANCE AND THEIR IMPACTS ON CUSTOMERS’ SATISFACTION ON MC DONALD'S PALU CITY - Gusti Andika Yudhistira; Wahyuningsih; Muzakir (JURNAL INTERNASIONAL UNIVERSITAS TADULAKO, 2023)
This research was conducted with the aim of testing and analyzing the effect of the utilization of digital marketing, market orientation and product innovation on marketing performance and their impact on customer satisfaction at McDonald's Palu City. This research was carried out using a quantitative descriptive analysis method with a sampling technique using Slovin. In this research, quantitative and qualitative data were used, and the data sources used were secondary data and primary data. The research population was the overall element of McDonald's visitors in August - December 2022 in Palu City, totaling 5,545. Based on the above calculations, the sample who became respondents of the research was adjusted to as many as 100 people or around 12% of the total visitors. Based on the research findings of the hypothesis testing that carried out in the research using partial last square analysis, it shows that the Utilization of Digital Marketing variable affects marketing performance, the Market Orientation variable affects marketing performance, the Product Innovation variable affects marketing performance, and the satisfaction variable mediates the relationship between the variables of the Utilization of Digital Marketing and Product Innovation on marketing performance while market orientation is not mediated.